Educational Leadership in Addressing the Challenges of Industry 5.0: A Bibliometric Analysis and Literature Review - Rachman, Forandra; Diana, Nirva; Wiliyanti, Vandan; Yetri, Yetri; Putri, Neza Navilla (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
The rapid emergence of Industry 5.0, characterized by human-centric innovation, advanced technologies, and human–machine collaboration, presents complex challenges for educational leadership. Educational leaders are increasingly required to create adaptive learning environments that prepare learners for future societal and workforce demands. This study examines the role of educational leadership in addressing the challenges of Industry 5.0 through a bibliometric analysis and systematic literature review. Bibliometric data were extracted from the Scopus database, comprising 75 publications published between 2007 and 2024, followed by an in-depth qualitative review of 40 highly relevant articles. Using the Bibliometrix package in R, the analysis generated three primary outputs: annual trends in scientific production, the most influential publications, and keyword co-occurrence networks. The findings reveal three dominant thematic clusters: (1) leadership in technology integration, (2) fostering creativity and innovation in learning environments, and (3) preparing students for future-oriented skills. Emerging but underexplored themes include emotional intelligence in leadership, ethical leadership, and inclusive approaches to technology adoption. This study provides a comprehensive overview of the intellectual structure of research on educational leadership in the Industry 5.0 context, offering a conceptual roadmap for scholars and practitioners seeking to strengthen leadership effectiveness in response to ongoing technological and societal transformations.